Cold atmospheric plasma induces ATP-dependent endocytosis of nanoparticles and synergistic U373MG cancer cell death - He, Zhonglei; Liu, Kangze; Manaloto, Eline; Casey, Alan; Cribaro, George P.; Byrne, Hugh J.; Tian, Furong; Barcia, Carlos; Conway, Gillian E.; Cullen, P.J.; Curtin, James F. (Nature Publishing Group, 2018)
Gold nanoparticles (AuNP) have potential as both diagnostic and therapeutic vehicles. However, selective targeting and uptake in cancer cells remains challenging. Cold atmospheric plasma (CAP) can be combined with AuNP to achieve synergistic anti-cancer cytotoxicity. To explore synergistic mechanisms, we demonstrate both rate of AuNP uptake and total amount accumulated in U373MG Glioblastoma multiforme (GBM) cells are significantly increased when exposed to 75 kV CAP generated by dielectric barrier discharge. No significant changes in the physical parameters of AuNP were caused by CAP but active transport mechanisms were stimulated in cells. Unlike many other biological effects of CAP, long-lived reactive species were not involved, and plasma-activated liquids did not replicate the effect. Chemical effects induced by direct and indirect exposure to CAP appears the dominant mediator of enhanced uptake. Transient physical alterations of membrane integrity played a minor role. 3D-reconstruction of deconvoluted confocal images confirmed AuNP accumulation in lysosomes and other acidic vesicles, which will be useful for future drug delivery and diagnostic strategies. Toxicity of AuNP significantly increased by 25-fold when combined with CAP. Our data indicate that direct exposure to CAP activates AuNP-dependent cytotoxicity by increasing AuNP endocytosis and trafficking to lysosomes in U373MG cells.